Existence of Acehnese expression in culture of Indonesian speech community - Muhammad Iqbal (Politeknik Negeri Bali, 2017)
The existence of the Acehnese expression in the culture of the Indonesian speech community is a sociolinguistic study. This study was aimed to describe the function of the Acehnese expression used by Indonesian speakers. Method of describing the existence of expression using qualitative approach of descriptive type. The Acehnese language expression data was collected from the informant using a note. The results of this study indicate that the Acehnese expression has a certain function in society so that the expression is used when communicating. The functions vary in order to establish loyalty, fairness, tranquility, and to maintain a balance of life. The Acehnese phrase exists in the Indonesian speaking community because it has a continuity between communication and its implementation in the life of society. The existence of this phrase is used as a social critique, guidance, and advice to strengthen unity and unity with in the framework of Indonesianc ulture. This expression exists for speakers of the Indonesian language because it contains the power of value that is a ble to educate speaker sunconsciously and thoroughly.